Survey on barriers to psychiatrists' use of clozapine for young people in Scotland and suggestions for reducing these. - Graham Walker; Jason Lang; Helen Smith (PLoS ONE, 2024)
Introduction The Mental Welfare Commission for Scotland published a report into the death of a young person, with recommendations for the Royal College of Psychiatry in Scotland Child and Adolescent Faculty; to explore if there were barriers to the use of Clozapine in young people in Scotland. Methods A mixed-methods study was performed using a cross-sectional survey of clinicians working in child and adolescent psychiatry across Scotland, to determine attitudes towards clozapine use and the perceived barriers and facilitators to clozapine treatment. Results Results suggest that there may be a lack of clearly defined pathways within and between services, as well as a lack of resources provided for the necessary monitoring of a young person started on clozapine. Multiple respondents felt unskilled in clozapine initiation and had not accessed formal training. The most frequently mentioned themes for improving facilitation of clozapine prescription were that of increased resources and training. Discussion National policymakers including the Mental Welfare Commission, NHS Education for Scotland, and NHS Scotland should consider these findings to address the potential underutilisation of clozapine for people aged under 18 in services across Scotland. A review of current service provision should take place, with consideration of whether the facilitators to clozapine prescription which our study has highlighted could be implemented more effectively. This may help reduce identified barriers and increase clozapine prescription to those who would benefit from it, potentially improving outcomes for young people with treatment-resistant psychosis.